2010
DOI: 10.1002/dvdy.22363
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac malformations in Pdgfrα mutant embryos are associated with increased expression of WT1 and Nkx2.5 in the second heart field

Abstract: Platelet-derived growth factor receptor alpha (Pdgfra) identifies cardiac progenitor cells in the posterior part of the second heart field. We aim to elucidate the role of Pdgfra in this region. Hearts of Pdgfra-deficient mouse embryos (E9.5-E14.5) showed cardiac malformations consisting of atrial and sinus venosus myocardium hypoplasia, including venous valves and sinoatrial node. In vivo staining for Nkx2.5 showed increased myocardial expression in Pdgfra mutants, confirmed by Western blot analysis. Due to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 43 publications
4
52
0
1
Order By: Relevance
“…This drainage pattern resembles the pattern observed in platelet-derived growth factor-receptor alpha (Pdgfra) knockout embryos Bax et al, 2010). Interestingly, expression patterns of Id2 resemble Fig.…”
Section: Venous Pole Abnormalitiessupporting
confidence: 71%
See 2 more Smart Citations
“…This drainage pattern resembles the pattern observed in platelet-derived growth factor-receptor alpha (Pdgfra) knockout embryos Bax et al, 2010). Interestingly, expression patterns of Id2 resemble Fig.…”
Section: Venous Pole Abnormalitiessupporting
confidence: 71%
“…Id2 knockout embryos demonstrated hypoplasia of the atrial myocardium and larger interatrial communications than observed in wildtype animals, a phenotype that was also observed in other models with impaired myocardial contributions from the posterior heart field, including the mice lacking podoplanin, Pdgfr-a, and Shox2 (Blaschke et al, 2007;Douglas et al, 2009;Bax et al, 2010). However, in contrast to observations in podoplanin and Pdgfra knockout embryos, atrioventricular septal defects were not observed in Id2 knockouts.…”
Section: Venous Pole Abnormalitiesmentioning
confidence: 56%
See 1 more Smart Citation
“…184,185 Furthermore, studies from mice show that mutated or absent PDGFRα, results in prenatal death and heart defects including thinned myocardium, and septa, valve, OFT, and aortic arch malformations. [186][187][188] In conclusion, part of the PDGF signaling system might be specifically coordinated by cardiac primary cilia, potentially in a network with Hh and other signaling pathways to coordinate cardiogenesis.…”
Section: Cardiac Primary Cilia and Coordination Of Pdgf Signalingmentioning
confidence: 95%
“…Our data also suggest that integrin activity at focal adhesions is required for the clustering of PE cells. Previous data has implicated Itgα4 as being essential for epicardial development particularly in regulating PE cell clustering, epicardial adhesion and epicardial migration (Sengbusch et al, 2002;Pinco et al, 2001;Yang et al, 1995;Dettman et al, 2003;Dokic and Dettman, 2006;Hirose et al, 2006;Pae et al, 2008;Bax et al, 2010). Integrin heterodimers have been shown to coordinate cytoskeletal interactions and adhesion with the surrounding ECM environment (Gardiner, 2011;Gehler et al, 2013;Huttenlocher and Horwitz, 2011;Manninen, 2015;Wolfenson et al, 2013), which are pertinent processes for epicardial formation and function (Kálmán et al, 1995;Nahirney et al, 2003).…”
Section: Lhx9-regulated Integrin Signaling Is Essential For Correct Fmentioning
confidence: 99%